The Importance of Awareness Checks to Prevent Early Detection of Breast Cancer in Young Women in Environment III New Exploration of Bamboo Fields - Rizky. A Bakara; Desi Anggreini (Institute of Computer Science (IOCS), 2020)
The purpose of this research is to find out the importance of Conscious Examination to Prevent Early Detection of Breast Cancer in Young Women. increase Knowledge about the Importance of Awareness Examination to Prevent Early Detection of Breast Cancer in Young Women. The types and forms of activities of this activity are the provision of material on the compliance of the Conscious examination to prevent Early Detection of Breast Cancer, knowing the signs of breast cancer. To achieve the objectives of the above activities, activities were carried out, including the delivery of material on contraceptives which is an effort to help couples of childbearing age to comply with the use of birth control pills.